The right to information in the ombudsman's agenda - Restrepo, Javier Darío (2022)
In the present article, the author will base the existence of the ombudsman on the right to information inherent to every citizen. Far from being a simply theoretical matter, the acknowledgement of this right obliges managers as well as journalists to stop feeling as if they were masters and owners of information and to consider media users from a point a view beyond that of the strictly commercial.